The Effect Of Paired Drill Training On The Ability Of Lower Passing Techniques In Volleyball Extracurricular Students Of SMP Negeri 20 South Bengkulu - Rostiana, Zizin; Retanza, Febra; Sumantri, Ajis (Educative Sportive, 2025)
This study aims to determine the effect of paired drill training on the ability of underhand passing techniques in volleyball extracurricular activities of students at SMP Negeri 20 Bengkulu Selatan. This study used a pre-experimental design method with the "One Group Pretest-Posttest Design" design, which is a design that uses pretest and posttest so that the difference in results due to the treatment given can be known with certainty. The population used in this study were students who took part in volleyball extracurricular activities at SMP Negeri 20 Bengkulu Selatan as many as 25 people and the research sample used a total side, which is a determination technique by taking the entire population as respondents or samples, namely 25 people. The statistical analysis used in this study was the t-test to test the hypothesis that there was an effect of paired drill training on underhand passing skills in volleyball extracurricular activities of students at SMP Negeri 20 Bengkulu Selatan. The results of the calculation analysis showed a significant effect on underhand passing results. The calculation results state that the calculation of the t-value calculation is -14-767 > ttable 1.714 with a level of α = 0.05, meaning that there is a significant influence between X (paired drill training) and Y (increased underhand passing) with a percentage of 39%. Based on the hypothesis testing that has been carried out, it states that there is a significant influence in the influence of paired drill training on underhand passing ability in the volleyball extracurricular activities of students at SMP Negeri 20 Bengkulu Selatan.